Outreach and Private Sector Partnerships Reduce Barriers to Female Market Participation and Financial Inclusion - CGIAR Research Program on Policies, Institutions, and Markets (2017)
This project involves an RCT designed to reduce barriers to women’s participation in cash crop value chains. The RCT promoted female participation in cash crop value chains by encouraging households to register outgrower sugar cane contracts in women’s names (which came with a requirement from the company that women have a bank account). By encouraging private sector processing companies and banks to interact with women, the project promotes women’s empowerment and improved rural welfare.